New Inner Product Quasilinear Spaces on Interval Numbers. (26th July 2016) - Bozkurt, Hacer; Yilmaz, Yılmaz
Abstract : Primarily we examine the new example of quasilinear spaces, namely, "I R n interval space." We obtain some new theorems and results related to this new quasilinear space. After giving some new notions of quasilinear dependence-independence and basis on quasilinear functional analysis, we obtain some results on I R n interval space related to these concepts. Secondly, we present I s, I c 0, I l ∞, and I l 2 quasilinear spaces and we research some algebraic properties of these spaces. We obtain some new results and provide an important contribution to the improvement of quasilinear functional analysis.